2014
DOI: 10.1161/circinterventions.114.001974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Real-Time Radiation Monitoring Device on Operator Radiation Exposure During Cardiac Catheterization

Abstract: Background— The Radiation Reduction During Cardiac Catheterization Using Real-Time Monitoring study sought to examine the effect of a radiation detection device that provides real-time operator dose reporting through auditory feedback (Bleeper Sv; Vertec Scientific Ltd; Berkshire, UK) on patient dose and operator exposure during cardiac catheterization. Methods and Results— Between January 2012 and May 2014, 505 patients undergoing corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Operator experience can significantly enhance radiation safety, 14 because it directly affects fluoroscopy time and patient dose, as shown in an analysis of the National Cardiovascular Data Registry. 15 The RadiCure trial 1 also showed remarkable variation of first operator radiation exposure among the 18 different operators that participated in the study. Our study suggests that addressing site-specific factors (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Operator experience can significantly enhance radiation safety, 14 because it directly affects fluoroscopy time and patient dose, as shown in an analysis of the National Cardiovascular Data Registry. 15 The RadiCure trial 1 also showed remarkable variation of first operator radiation exposure among the 18 different operators that participated in the study. Our study suggests that addressing site-specific factors (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…16 Similarly, there are guidelines for reducing radiation exposure in the cardiac catheterization laboratory. 17 In our opinion, best practices for reducing operator radiation dose include: (a) low frame per second fluoroscopy (7.5 frames per sec or lower); 24 (b) using the fluoro-store function of the X-ray equipment instead of cine-angiography whenever possible; (c) optimizing patient and equipment positioning, by maximizing the distance between the patient and the X-ray tube, minimizing the distance between image intensifier and the patient 18-20,32 and avoiding extreme angulations 22,23 ; (d) collimation; 18-20 (e) shielding, both fixed and disposable (such as the Radpad, Worldwide Innovations & Technologies, Inc), 33 thyroid collar, leaded glasses for eye protection as well as radiation protective hats; 25-28 (f) using radiation monitors that provide real time feedback; 1 and (g) using newer X-ray systems that reduce patient (and operator) radiation dose. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study 1 demonstrated that many physicians do not routinely wear their radiation badge, so that their exposure is unmeasured or falsely low, lest they be banished from the laboratory, although there is a clear evidence showing that wearing the dosimeter leads to lower operator and patient exposure. 13 Adoption of radiation safety protocols 14 and improved radiation equipment and imaging 10 to decrease dose have been effective, but the major motivation is to allow longer procedures without the patient being exposed to dangerous levels. Newer ideas, such as ceiling suspended aprons, and shielded gloves and caps, continue the concept of individual protection, rather than propose a new paradigm.…”
Section: See Article By Andreassi Et Almentioning
confidence: 99%
“…Stochastic effects are caused by random cell damage where probability is proportional to received radiation dose without any threshold. Of these effects, the oncological risk11 is of concern as the latency period after exposure can be over 40 years,12 and ways to minimise radiation have been afforded increasing attention 13 14…”
Section: Introductionmentioning
confidence: 99%